A potentially new phase of the cardiac cycle: Pre-isovolumic contraction recognized by echocardiography. Issue 21 (May 2018) - Cong, Zhibin; Jiang, Bin; Lu, Jianbo; Cong, Yunyi; Fu, Jili; Jin, Mingyue; Wang, Xue
Abstract : Abstract: Clinically the isovolumic contraction time (IVCT) can be measured by 3 echocardiographic methods of M-mode, pulse-wave Doppler (PWD), and tissue Doppler imaging (TDI). But IVCT can be clinically different by the 3 methods. This study is to investigate whether there is a potentially unidentified phase causing the discrepancies by analyzing electric mechanical delay time (EMD), IVCT, and pre-ejection period (PEP). A total of 30 healthy subjects were recruited for the study. EMD, IVCT, and PEP were obtained by the 3 methods, respectively. MCT (the interval from the onset of the QRS wave to the closure point of the mitral valve measured by TDI) and ICMC (the interval from the onset of IVC wave S1 to the closure point of the mitral valve measured by TDI) were both measured by color TDI. IVCTt (IVCT measured by TDI) was significantly longer than IVCTm or IVCTd (IVCT measured by M-mode or PWD) (both P < .0001), while EMDt (EMD measured by TDI) was significantly shorter than EMDm or EMDd (EMD measured by M-mode or PWD) (both P < .0001). But MCT was not significantly different from EMDm or EMDd ( P > .05) and ICMC did not differ significantly from EMDm or EMDd minus EMDt or IVCTt minus IVCTm or IVCTd ( P > .05), in other words, ICMC almost equaled to (EMDm or EMDd minus EMDt ) or (IVCTt minus IVCTm or IVCTd ). There may be an unidentified phase between the end of atrial contraction and the closure of mitral valve causing the discrepancies in IVCT, which is named as the pre-isovolumic contraction phase. It is a non-isovolumic phase and is included in the traditional isovolumic contraction phase.